Controle, Sequestro e Sedução da Subjetividade no Sistema ONA da Qualidade - Cioli, Rejane (2018)
This research had as object of critical investigation, comprehend how the speeches and practices in quality management, established by the respective system of the National Accrediting Organization (ONA), can result in creating sophisticated controlling mechanisms of managers subjectivity and work relations as currently performed by the hospitals. These instruments, used to increase and exploit theservice production and its workers, have been following the changes in this area and developing increasingly improved structures, especially because of the connection between managing technologies and the flexible production method. By investing in management strategies these organizations go beyond the control of physical aspects of workers, reaching not only their body but also their mind and emotions, to guarantee, in a very subtle way, their voluntary taming and submission that meet the organizations interests and ideologies. The control of subjectivity in its hidden and manifested instances, has been contributing to intensify the workers and the work process exploitation, making it possible to appropriate their individual freedom, in order to submit them to the knowledge, values and organizational ideologies and then, kidnap their subjective world. The reports of quality managers, who work at accredit hospitals with excellence by ONA system in Curitiba, were obtained in semistructured interviews and submitted to Dialogical Discourse Analysis. Throughout this research, it was possible to identify that the organizations have been using empowerment strategies, recognition, participation and professional satisfaction to generate feelings of proud, contribution, partnership, sense of belonging and, in some cases, enchantment and seduction of quality managers. They also act by the speech of excellence and improvement of quality performance and its resulting mechanisms, in order to have the control and voluntary subsumption of managers to their own ideology and organization interests and to kidnap, in very specific circumstances, the workers’ subjectivity. Because they identify themselves with the organization ideals, by enchanting and seduction processes, the managers of quality lose the consciousness of the established level of commitment and the ability to define priority to themselves and in this way, unconsciously implementing, the kidnap of their subjectivity, promoting the working exploitation. Finally, it was found that knowing the quality system contradictions, makes it possible for the managers to assume consciously and deliberately the conditions where they have been inserted, and, in this way, build more balanced and satisfying relations.